2014
DOI: 10.1111/ctr.12357
|View full text |Cite
|
Sign up to set email alerts
|

The role of mammalian target of rapamycin inhibitors in the management of post‐transplant malignancy

Abstract: Post-transplant malignancies, which occur either de novo or as cancer recurrences, are due to chronic exposure to immunosuppressive agents and are often more aggressive than those that develop in the non-transplant setting. Mammalian target of rapamycin (mTOR) inhibitors have antitumor and immunosuppressive effects. The dual effects of this class of agents may provide adequate immunosuppression to prevent organ rejection while simultaneously reducing the risk of post-transplant malignancy. mTOR inhibitors have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 93 publications
(104 reference statements)
0
14
0
1
Order By: Relevance
“…Recent published reviews have assessed the evidence base relating to mTOR inhibitors overall [17, 36] but the two available agents, sirolimus and everolimus, are not necessarily interchangeable [37]. This article examines the available data and considers the role of everolimus in malignancy after organ transplantation from the clinician's perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Recent published reviews have assessed the evidence base relating to mTOR inhibitors overall [17, 36] but the two available agents, sirolimus and everolimus, are not necessarily interchangeable [37]. This article examines the available data and considers the role of everolimus in malignancy after organ transplantation from the clinician's perspective.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, regression of KS with less risk to the graft has been obtained by switching from calcineurin inhibitors (CNI) to sirolimus which is now considered the first‐line treatment of KS for transplant recipients . The patient with KS in this report was successfully treated by switching from tacrolimus to sirolimus which studies have shown is associated with a lower incidence of malignancy in the posttransplant period …”
Section: Discussionmentioning
confidence: 92%
“…Osimertinib is an oral, third-generation EGFR-TKI designed to target the EGFR T790 M mutation (1)(2)(3). Osimertinib is primarily eliminated in feces (68%) and, to a lesser extent, in urine (14%) (4).…”
Section: Efficacy and Safety Of Osimertinib In A Hemodialysis Patientmentioning
confidence: 99%
“…To the Editor: The risk of developing renal cancers is reportedly 3-5% among patients with end-stage renal disease pre-and post-transplantation, which is 100-fold higher than that among the general population (1). Immunosuppressive therapies, which are administered to prevent graft rejection, increase the risk of developing cancers or accelerate tumor cell growth (2). Currently, the treatment strategy for metastatic renal cell carcinoma (mRCC) consists of molecular-targeted therapy.…”
mentioning
confidence: 99%